Role of ultrasonography and inflammatory markers in predicting complicated appendicitis - Arka Banerjee; Simmi K Ratan; Sujoy Neogi; Binita Goswami; Rashmi Dixit; Shasanka Shekhar Panda (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim is to compare the diagnostic accuracy of laboratory investigations and ultrasonography (USG) in distinguishing complicated appendicitis (C-AA) from uncomplicated appendicitis (UC-AA). Materials and Methods: Forty-six children who underwent appendicectomy at our center between November 2018 and July 2020 were included. Based on intraoperative findings, they were divided into two groups - complicated (perforated, gangrenous, or associated with fecal peritonitis; n = 18) and UC-AA (n = 28). USG findings and inflammatory markers were compared in both groups at admission. Results: At admission, the mean values for total leukocyte count (TLC) (16090.56 vs. 11739.29 per mm3), high sensitivity C-reactive protein (hsCRP) (35.8 vs. 31.62 mg/L), and procalcitonin (PCT) (3.83 vs. 1.41 ng/mL) were significantly higher in C-AA. Visualization of a blind tubular aperistaltic structure was the only sonographic sign showing statistical significance - significantly lower in C-AA (50% vs. 90%). Independent predictors of C-AA were - duration of symptoms >48 h (odds ratio [OR] 6.3), free fluid/loculated collection in right iliac fossa (OR 3.75), TLC >11000/mm3 (OR 3.6), hsCRP >35 mg/L (OR 6.0), PCT >0.6 ng/mL (OR 4.02), and nonvisualization of appendix on USG (OR 8.33). Biochemical factors were sensitive (89%) and specific (55%) in differentiating C-AA from UC-AA but the addition of sonological parameters significantly improved the specificity of predicting complicated AA to 61% (P = 0.0036). Conclusion: Combining laboratory data with sonological findings significantly improves the predictive value for differentiating C-AA from UC-AA and can help decide operative approach and prognosticating.